Educational inequalities and success in Asian countries in PISA 2009 (Foro de Educacion, 2011)
This article discusses the results of PISA 2009 from seven Asian countries. The analysis focuses on three hubs of educational inequality: academic inequalities, inequalities by gender and social in- equalities. The main conclusion drawn from the results of this work is that is not possible to affirm that Asian education systems constitute a homogeneous educational model.